Spindle cell carcinoma of maxilla: Histomorphological and immunohistochemical analysis of a case - Rath, Rachna (Medknow Publications & Media Pvt Ltd, 2014)
The intriguing array of spindle cell lesions occurring, especially in the head and neck region, poses a critical diagnostic challenge not only to the histopathologist but also ultimately to the clinicians for planning an appropriate treatment protocol. Overlapping spectrum of clinico-radiographic and microscopic features further compounds this problem. In such situations, the aid of ancillary techniques like immunohistochemistry (IHC) is sought to clinch the diagnosis. But is the diagnosis based on IHC most decisive? Probably the answer lies in the Pandora's Box. This paper analyzed the potential doubts, apprehensions and the reliability that is singularly based on the morphological spindle appearance of an abnormal cell that has deviated from the usual clinical and microscopic presentation and thus posed a diagnostic dilemma warranting more questions than the answers. We review the etiopathogenesis of this entity and its differential diagnosis from few other spindle cell lesions of head and neck with special reference to use of immunohistochemical markers, with a case study.